Парни в бронежилетах: [роман] / Сергей Самаров - Самаров Сергей Васильевич (Спецназ ГРУ, 2004)
Экземпляры: ф.12 (20180326) / Инвентарный номер: 58177 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: С 17 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44